Medical care payment improvement within diagnosis-related groups of patients with severe asthma requiring biologic disease-modifying drugs by regional adaptation mechanism in the Moscow Region - A. D. Ermolaeva; V. S. Krysanova; T. N. Ermolaeva; K. I. Polyakova; K. A. Kokushkin (IRBIS LLC, 2021)
Objective: scientific rationale of changing approaches to medical care payment for hospitalization of patients suffering from severe asthma (SA) that require the prescription of biologic disease-modifying drugs (bDMDs) within the constraints of diagnosis-related groups (DRGs) on the level of the Moscow Region.Material and methods. For the federal model regional adaptation, the authors used the mechanism of subgroups selection in the structure of basic DRG No. 336 st36.003 and No. 139 ds36.004 "Treatment with biologic disease-modifying drugs and selective immunosuppressants" in the round-the-clock (RH) and day-time hospital (DH). Budget impact analysis (BIA) was performed to provide scientific and economic feasibility for the improvement of medical care payment for bDMDs proscribed to patients with SA within DRG at the level of the Moscow Region.Results. The analysis of cost of drug therapy and medical services per 1 case of hospitalization of patients with SA, that required bDMDs therapy, considering the classification criterion (international nonproprietary name of drugs and drug therapy regimens), showed 10 subgroups in DRG No. 336 st36.003 (level 1) and 9 subgroups in DRG No. 139 ds36.004. Expert estimates on the rate of hospitalizations and drug dosage regimen indicated for patients with SA were used to calculate the relative cost weights (CW). The highest CW was observed in the subgroup that received benralizumab in RH (CW=7.46) and in DH (CW=12.08) conditions. BIA demonstrated 110,103,901.53 rubles (or 31%) budget savings for the health care system of the Moscow Region.Conclusion. The implementation of the adapted DRG federal model in the conditions of the health care system of Moscow Region is an economically feasible approach to the organization of the inpatient medical care provided to patients with SA needing bDMDs prescription.